COVID-19 Impact and Psychological Adjustment Among College Students: Variability Across Race/Ethnicity and Generational Status. Issue 3 (2nd September 2022) - Fletcher, Anne C.; Alligood, Brittany N.; McCurdy, Amy
ABSTRACT: College students ( N = 619) self-reported psychological and resource impact of COVID-19, self-esteem, and depressive symptoms. Greater COVID-19 impact was associated with more depressive symptoms and lower self-esteem. First-generation students reported greater resource-related COVID-19 impact. Among continuing-generation students, Black students reported greater resource impact than White students. The positive association between economic COVID-19 impact and depressive symptoms was stronger for Black first-generation students than for White first-generation students or White continuing-generation students. The positive association between COVID-19 psychological impact and depressive symptoms was particularly strong among continuing-generation White students and was stronger among first-generation White students than continuing-generation Black students.